Influence of Abutment Stiffness and Strength on the Seismic Response of Horizontally Curved RC Bridges in Comparison with Equivalent Straight Bridges at Different Seismic Intensity Levels - Khashayar Heydarpour; Payam Tehrani (Shock and Vibration)
Seismic design codes have imposed some limitations on the maximum subtended angle of curved bridges and allow engineers to analyze and design them using an equivalent straight bridge. This paper investigates these limitations and evaluates the AASHTO code recommendations regarding the prediction of the seismic responses of curved bridges using an equivalent straight bridge for bridges with different abutment properties at different seismic hazard levels. In this regard, the seismic responses of 21 horizontally curved and straight RC four-span bridges with different abutment types are investigated. In 7 bridge models, soil-abutment-bridge interaction is neglected, while in the rest of the bridge models, the seat-type abutments with the participation of the nonlinear backfill soil, gap, and abutment piles are used in structural modeling. First, nonlinear static (pushover) analyses are carried out to evaluate the overall behavior of the bridges with different abutment configurations in the two perpendicular principal directions. Subsequently, nonlinear time history analyses are performed to predict the seismic response of bridge elements, including column drifts and deck displacements at the place of the abutments in the radial and tangential directions at different seismic intensity levels, including the design basis earthquake (DBE) and maximum credible earthquake (MCE) excitation levels. In addition, the actual maximum displacements of the components of the bridges (i.e., the total absolute displacements) were also predicted and evaluated for different cases. It was found that the abutment properties and boundary conditions had a significant effect on the seismic response assessment of curved bridges compared to straight bridges, while such parameters are not currently considered by the design codes. The results also indicated that by increasing the seismic intensity level, more limitations should be imposed on the use of the equivalent straight bridges.